The Fault At The End Of The Tunnel - S. S. Rowland (International Conference on Ground Control in Mining, 1994)
Good afternoon, ladies and gentlemen. It is a pleasure, for several reasons, to be here at this 13th International Conference on Ground Control in Mining. Of course it's always a pleasure to be able to see and reacquaint myself with many long-time friends; but it's also a pleasure, or 1 should say worthwhile, because I take something back with me, some knowledge about mining that lets me do my job better and more safely. if I can do that, I've accomplished my purpose in being at a conference such as this. This conference is a little different, though. I have to earn my stay. I have to earn it by telling you a story; a story about mining through a mile of rock to get from one coal seam to the same seam on the other side of an ancient river channel; a story about mine personnel taking over the job from a contractor; a story about having to mine through two faults after the hard part was supposed to be over, but, most importantly, it's a story about how it was accomplished successfully and safely by a group of ordinary coal miners possessed with determination, belief in themselves, and a "can do" attitude. If you can take any part of my story and use it to do your job better and more safely, then I will have accomplished my purpose in being here today. Kerr-McGee Coal Corporation's Galatia Mine is located in Southern Illinois near the town of Harrisburg in Saline County, about 350 miles south of Chicago and 120 miles southeast of St. Louis. Construction of the mine began in 1982, and the first coal was shipped in 1984 from the Harrisburg No. 5 Seam, 550' below the surface. Mining began in the Herrin No. 6 Seam, 100' above the No. 5 Seam, on April 1, 1985. Mining in both seams began by using the room-and-pillar method. In 1989, the No. 6 Seam was converted to longwall mining, as was the No. 5 Seam in 1992. Today, all mining is done by the longwall method except for the required development work, which is performed by continuous miners. A heavy-media preparation plant with a 4.2 million-ton annual clean-coal capacity processes the coal. By the end of 1994, with annual production now exceeding 4 million tons, we will have shipped over 30 million tons of steam and metallurgical coal throughout the United States and the world. Most of the coal has been used as the primary source of fuel to generate electricity for the city of St. Louis. The No. 5 Seam coal can be used as a semi-soft coking coal or as a high-Btu, relatively low-sulfur steam coal. Its use allows utilities to comply with Phase I of the Clean Air Act Amendments of 1990 without installing flue gas desulfurization units or blending with other coals. The Herrin No. 6 Seam is a high-Btu, medium-sulfur steam coal that requires blending to meet Phase I requirements. Because the No, 6 Seam coal does not meet the Clean Air Act Amendments' Phase I compliance standards, we were forced to cease mining operations in the No. 6 Seam, leaving 170,000,000 tons of minable coal in the ground. Last month the Galatia Mine became a single-seam operation mining the Harrisburg No. 5 Seam only. The Clean Air Act Amendments of 1990 and the resultant S02 emission limitations on electrical power generation plants effectively eliminate, beginning in 1995, the near-term potential for profitable mining of the Galatia Mine's high sulfur Herrin No. 6 Seam coal. Because of the Clean Air Act Amendments, it is virtually impossible to market high-sulfur coals like the No. 6 coal unless the mine location and mining conditions enable greatly depressed sales prices to cover costs. We, along with the majority of